2022
DOI: 10.1039/d2tb01269c
|View full text |Cite
|
Sign up to set email alerts
|

A combination of a graphene quantum dots–cationic red dye donor–acceptor pair and cucurbit[7]uril as a supramolecular sensor for ultrasensitive detection of cancer biomarkers spermine and spermidine

Abstract: In a unique approach, the combination of a donor-acceptor pair of hydroxy graphene quantum dots (GQDs-OH) and a red-emissive donor-two-acceptor (D-2-A) type dye with pyridinium units (BPBP) and the well-known...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The products were characterized by 1 H NMR, 13 C NMR, IR, and HRMS analyses. The NMR spectra of the synthesized compounds matched well with the reported data, indicating their successful formation. , The substrate scope was studied with both electron-rich (Scheme , entries 3a–3c ) as well as electron-deficient systems (Scheme , entries 3d , 3e ). It was observed that in the presence of EDGs at the para position of the −OH, the di-formylation occurs solely at both the ortho positions, and the reactions were completed within 2 h with the yield in the range of 80–90%, making this mechanochemical method a facile tool for di-formylation as well (Scheme ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The products were characterized by 1 H NMR, 13 C NMR, IR, and HRMS analyses. The NMR spectra of the synthesized compounds matched well with the reported data, indicating their successful formation. , The substrate scope was studied with both electron-rich (Scheme , entries 3a–3c ) as well as electron-deficient systems (Scheme , entries 3d , 3e ). It was observed that in the presence of EDGs at the para position of the −OH, the di-formylation occurs solely at both the ortho positions, and the reactions were completed within 2 h with the yield in the range of 80–90%, making this mechanochemical method a facile tool for di-formylation as well (Scheme ).…”
Section: Resultssupporting
confidence: 73%
“…The di-formyl aromatic compounds have been used as starting materials for the synthesis of a variety of dyes as well as they have found their use in supramolecular chemistry. , The same substrate ( 1a ) was used as a model substrate for the optimization of the conditions of the di-formylation reaction. First, the amount of HMTA was doubled to 2 equiv and H 2 SO 4 to 5 equiv, respectively, and it was observed that the reaction proceeds well with 56% of the di-formylated product 3a and a small amount of 2a (Table S3, Supporting Information, entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…161,243 Furthermore, many studies employing DFT calculations model GQDs as monolayer and small-sized structures for the sake of computational convenience when explaining the structure and band gap of GQDs. 244,245 Therefore, the issue of self-assembly of GQDs cannot be ignored, and it is essential to consider methods to mitigate aggregations of GQDs. Two primary strategies are available for this purpose, as follows.…”
Section: Controlling Self-assembly Of Gqdsmentioning
confidence: 99%
“…Macrocyclic structures are frequently involved in supramolecular host–guest interactions, which have been established as recognition units in the sensing assembly. 102 The non-covalent trapping of analytes as guest molecules in the host cavity serves as the basis for the molecular recognition process for the majority of macrocyclic hosts. These macrocycles are chemically stable, simple to functionalize, and are excellent receptors for a variety of analytes as guest molecules.…”
Section: Azines In Supramolecular Sensingmentioning
confidence: 99%